THE STUDENTS’ PERCEPTION OF WHATSAPP APPLICATION IN ENGLISH LANGUAGE LEARNING DURING MOVEMENT CONTROL ORDER (MCO) - Ong Elly; Rafidah Abd Karim, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Movement control order (MCO) was implemented in the country from 18 March 2020 until 3 May 2020 and followed by conditional movement control order (MCO) from 4 May 2020 until 9 June 2020 that cause the public universities to adapt to online and distance learning (ODL). More studies on using the WhatsApp application to learn English language from the perspective of the learners are needed because of the physical distancing rules adapted to contain Covid-19 pandemic. The purpose of the study is to investigate the learners’ perception towards learning English language using the WhatsApp messenger application during movement control order (MCO). The data was collected by an online questionnaire which was given to 223 students in a selected public university. The results showed that the WhatsApp messenger application is found to be a popular choice of smartphone application for communication among the participants. The participants also believed that the WhatsApp application is thought not to be used for searching information, not for understanding complex concepts, slows down when multiple files are uploaded or downloaded, slows down when multiple video calls are conducted and known not to stress users. It can be concluded that the WhatsApp application is a good platform for English language learning as communication is the purpose of using language.